The Effectiveness Of Using Video In Teaching English Vocabulary At The Eight Grade Of Smp N 1 Kalijambe In 2014/2015 Academic Year - Priyandana, David Fajar; , Aryati Prasetyarini, S.Pd, M.Pd; , Drs. Djoko Srijono, M.Hum (2015)
As a foreign language in Indonesia, English is learned seriously by many people to have a good prospect in the community of international world. Recently, English becomes important. Since it is important, English is taught widely at formal schools starting from elementary school up to universities, even at informal schools i.e. course. In teaching English, mastering vocabulary is very important because by mastering it, the student will easily catch information delivered in English. Without knowledge about vocabulary, the students can not develop their the English skill. In teaching learning process we can elaborate about the technology and education with Media especially using digital video. Because teaching is a performance-based profession, teacher of education programs commonly integrate classroom-based instruction with field-based practice. Based on the problem statement, the purposes of this study are :To know whether teaching vocab using video is more effective than that without media. The type of research is quantitative research. The method is quasiexperimental designs, how experimental method is ideal for determining cause and effect. Based on the analysis performed using t-test on SPSS 16.0 for windows program, then it is obtained significant value 0.000 with 0.000 < 0.05. It means that Ha is accepted. In other words the learning process using video can make students easily learn vocabulary rather than learning without using video medi. From the research result it can be understood that hypothesis is accepted, learning process using video media, is more effective in the vocabulary understanding than learning without video media.